The role of minor alloying in the plasticity of bulk metallic glasses. (November 2020) - Hilke, Sven; Rösner, Harald; Wilde, Gerhard
Graphical abstract: Abstract: Micro- or minor alloying of metallic glasses is of technological interest. An originally ductile Pd-based monolithic bulk metallic glass (Pd40 Ni40 P20 ) was selectively manipulated by additions of Fe or Co. The alloying effects were extreme, showing either exceptional ductility upon Co addition or immediate catastrophic failure upon Fe addition when tested under uniaxial compression or 3-point bending. The amorphous structure was characterized prior to deformation with respect to its medium-range order (MRO) using variable resolution fluctuation electron microscopy (VR-FEM). We observe striking differences in the MRO between the ductile and brittle metallic glasses, with the ductile glasses exhibiting a rich structural diversity and MRO correlation lengths up to 6 nm. The MRO diversity seems to enable easier shear banding and hence enhance the deformability.